Diagnosis of Brugada syndrome affects quality of life and psychological status - Berne, Paola; Usai, Francesca; Silva, Etelvino; Melis, Irene; Fancello, Tatiana; Onida, Alessandra; Merella, Pierluigi; Figus, Francesco; Brugada, Josep; Casu, Gavino (Frontiers in Cardiovascular Medicine, 2024)
Background Chronic diseases have a negative impact on quality of life (QOL) and psychological health. There are limited related data regarding this topic in Brugada syndrome (BrS). We evaluated the effects of the diagnosis of BrS on health-related QOL and psychological status among patients and their relatives. Methods Patients with BrS and their relatives underwent psychological evaluation at diagnosis (T0), 1 and 2 years after diagnosis (T1 and T2) using questionnaires on mental QOL, anxiety, depression, stress, post-traumatic stress, and resilience resources. Results Sixty-one patients and 39 relatives were enrolled. Compared with controls, patients showed increased physical QOL (54.1 ± 6.5 vs. 50.1 ± 8.0, p = 0.014), reduced mental QOL (43.2 ± 11.8 vs. 49.6 ± 9.1, p = 0.018) and increased anxiety (9.9 ± 6.6 vs. 6.9 ± 7.7, p = 0.024) at T0; reduced resilience scores (3.69 ± 0.40 vs. 3.96 ± 0.55, p = 0.008) at T1; and reduced resilience (3.69 ± 0.35 vs. 3.96 ± 0.55, p = 0.019) and increased anxiety scores (16.4 ± 12.8 vs. 6.9 ± 7.7, p = 0.006) at T2. Relatives presented higher stress (17.63 ± 3.77 vs. 12.90 ± 6.0, p = 0.02) at T0 and higher anxiety scores at T0 (13.5 ± 7.6 vs. 6.9 ± 7.7, p < 0.001), T1 (12.0 ± 8.7 vs. 6.9 ± 7.7, p = 0.005), and T2 (16.4 ± 12.8 vs. 6.9 ± 7.7, p = 0.006) than controls. Female sex was significantly independently associated with worse mental QOL scores in patients at T0 (odds ratio = 0.10; 95% confidence interval = 0.05–0.94; p = 0.04). Conclusions The diagnosis of BrS impairs the QOL and psychological status of patients and their relatives. Female sex is independently associated with worse mental QOL in patients at diagnosis.